Rekonstruksi Ideologi Superioritas Laki-Laki sebagai Penerima Wahyu (Analisis kata Rijalan pada QS. al-Anbiya' ayat 7 dengan Metode Ma’na Cum Maghza) - Akmal, Saiful (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Previous interpretation of QS. al-Anbiya’ ayat 7 states that this verse is the argument that the messenger is only from men. However, it turns out that the word rijāl in QS. al-Anbiya’ ayat 7 there are indications of the meaning of women which is correlated with rijāl in other verses in the Koran. This shows that there are differences in interpreting interpretations depending on the interpreter's period. This study aims to examine the historical meaning, historical significance, and contemporary dynamic significance of QS. al-Anbiya’ ayat 7 to find relevant and progressive meanings to the present. This research was assessed using qualitative methods. literature review comes from data sources related to research with the ma'nā cum magzā approach theory. This theory was chosen because it has a structured and comprehensive work tool in offering interpretations of the Koran, because it has united classical science with multidisciplinary knowledge. This research got the result that QS. al-Anbiya’ ayat 7 actually does not focus on the issue of apostolic identity, but this verse indicates a connection with the statement of the Quraysh who doubted the Prophet Muhammad SAW as a messenger, then, in terms of historical significance, the message of the verse is an affirmation that the Prophet Muhammad SAW receiving revelation and in terms of contemporary dynamic significance reveals the importance of having competence in preaching which includes several strategies to approach aspects of sociology, psychology, culture and the wise command to ask scientific professionals who are experts in their fields.